Study of resistant peculiarities of Juniperus sabinaand Juniperus communis in the conditions of Zhezkazgan industrial region - Maksutbekova G.Т. (Fundamental and Experimental Biology, 2019)
At the article the results of assessment of winter-resistant, drought-resistant and gas-resistant of Juniperus sabina and Juniperus communisin the conditions of cities Zhezkazgan and Satpayev are conducted. Winter resistance indicators for kazak juniper were 5 points, for common juniper — 4 points; drought resistance of kazak juniper — 5 points, common juniper from 3 to 4 points. The results are shown that in the territory of the Zhezkazgan copper plan there is more damage to the leaf plates of wood plants than in the experimental comparison site of the Zhezkazgan Botanical Garden (the main arboretum). Thus, the percentage of damage was 2–2.5 times different. Kazak juniper is classified as highly gas-resistant culture, while common juniper is classified as weakly gas-resistant. This fact can be explained by the fact that the first species grows in the local natural flora — in the mountains of Ulytau, while the second species — introduced from the Main Botanical Garden (Almaty city). According to the results of many years of research kazak juniper is classified as very promising plants, that is, it can be widely used in mass greening of settlements of the Zhezkazgan region. Juniper common will be classified as promising species suitable for greening with squirrel and parks under the condition of regular watering.